Kinetic Study on the Process of Cyclopentane plus Methane Hydrate Formation in NaCl Solution - Lv, Qiunan; Song, Yongchen; Li, Xiaosen (Energy & Fuels, 2016)
In this work, the formation kinetics of cyclopentane (CP) + methane hydrate is studied. CP is used as a promoter to accelerate the hydrate formation. The total methane consumption, the induction time, and the formation rate were investigated under different hydrate formation conditions in NaC1 solution. The results indicated that the pressure driving force could increase the gas consumption and shorten the induction time. Meanwhile, the induction time could be greatly influenced by the pressure driving force at a lower temperature. Especially, it could be shortened to a minimum value of 110 s with the increase of the pressure driving force at a fixed operating condition (CP concentration, 7.45%; NaCl solution concentration, 3.50%; and temperature, 298.15 K). Moreover, the hydrate formation rate would be accelerated with the increase of the stirring rate by its promotion in the dissolution and dispersion of methane. Finally, a higher CP concentration was favorable for the rapid hydrate formation of CP + CH4 binary hydrates. The amount of CP used could determine the amount of methane incorporated into the hydrate phase.